Injury Prevention Program among Athletes in Malaysia: A Systematic Review - Shaharudin, Muhammad Iqbal; Ahmad Yusof, Hazwani (IIUM Medical Journal Malaysia, 2025)
Sport is responsible for the significant occurrence of acute and overuse injuries among athletes. The injuries during sport can result in long-term negative consequences that reduces the performance of sports. The burden of sport-related injuries is substantial, and there is a lack of studies assessing the effectiveness of injury prevention strategies. To date, cumulative information regarding injury prevention strategies is limited in Malaysia. This study aims to identify the characteristics of injury prevention programs among athletes in Malaysia. This research was systematically conducted utilising the electronic databases of Web of Science (WoS), Scopus, ClinicalKey, Cochrane Library, PubMed, SPORTDiscus, and Google Scholar. Two reviewers, MIS and HAY, independently selected articles based on the established inclusion criteria from 1st January 2015 to 31st December 2024. The study followed PRISMA guidelines and was registered with PROSPERO under registration number CRD42024513383.Nine eligible papers were included in the study and scored at least five points on the 11-point checklist of the CASP appraisal tool. Injury prevention programs, including neuromuscular training and sport-specific interventions, enhance strength, flexibility, and balance, reducing injury risk among athletes. It is recommended that injury prevention programs be adopted in every sport, especially during warm-up periods of training sessions. Future research should focus on individualised programs and technology for real-time feedback injury prevention strategies.